MENGGUNAKAN DAN MENGINTERPRETASIKAN EXPLORATION FACTOR ANALYSIS: PANDUAN BAGI PENELITI DAN MAHASISWA - Adnan Sauddin (Teknosains, 2014)
How should we draw the relationship between each variable in a study included a number of variables, especially research that is very much. A simple question, but it will have a profound effect on the validity of the research is not done. Factor analysis is a statistical analysis technique that can help conduct research on a set of variables in the grouping factors, where each variable in the variable has a large variance. The use of statistical science as a tool to analyze, especially if the use of statistical science aided by using software such as Minitab, SPSS, SAS. That uses software to calculate statistics, an expression of "whatever we put in a certain statistical software will still produce something in the form of numbers", the question is whether the resulting output is valid or not? These are important questions. Therefore, in this article provided a good explanation of the theory of mathematical statistics, along with the use of software (Minitab) to facilitate the calculation process, also given the interpretation of the results obtained.